The complex interplay of physician, patient, and spouse in preoperative counseling for radical prostatectomy: a comparative mixed‐method analysis of 30 videotaped consultations. Issue 8 (3rd December 2015) - Huber, Johannes; Streuli, Jürg C.; Lozankovski, Novica; Stredele, Regina J. F.; Moll, Peter; Hohenfellner, Markus; Huber, Christian G.; Ihrig, Andreas; Peters, Tim
Abstract: Objectives: Spouses of cancer patients play a crucial role in deciding on therapeutic choices. The aim of our study was to assess their role in counseling for radical prostatectomy. Methods: We analyzed 30 videotaped preoperative consultations prior to radical prostatectomy. Thereof, 14 included the patients' female partner and 16 took place without partner attendance. We performed quantitative and qualitative conversation analysis to compare both settings. Results: Mean age of patients was 61 (47–73) years; 13% (4/30) did not have a partner. Duration of preoperative consultations was 20 (10–32) min. Physicians spoke most of the time (93%, range 71–99%), followed by patients (7%, range 1–20%) and spouses (2%, range 0–8%). Patients whose spouse was present at the consultation tended to have a more averted posture (50% vs. 25%, p  = 0.04) and tended to speak less often (5% vs. 8%, p  = 0.02). In 4 of 14 (29%) consultations, the spouses tended to be more dominant, speaking more frequently. Qualitative analysis showed several examples of emotional support and helpful contributions by spouses. Difference of opinion occurred when pros and cons of a nerve‐sparing approach were discussed. The spouses' impact appeared to influence the final decision of men contemplating a nerve‐sparing approach in 1 of 14 conversations. Conclusions: Spouses appear to play a complex and sometimes ambivalent role in counseling for radical prostatectomy. Especially when discussing a nerve‐sparing approach, urologist should focus on the patients' true needs while interacting with both partners. Personalized decision aids might help to identify possible conflicts in advance.Copyright © 2015 John Wiley & Sons, Ltd.